2014
DOI: 10.4304/jltr.5.5.1167-1175
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between EFL Learners’ Metacognitive Strategies, and Their Critical Thinking

Abstract: Abstract-The present study investigates the the relationship between metacognition and critical thinking in language learning. 102 intermediate students from 2 language institutions in Rasht were selected. Data were gathered by means of two questionnaires and were analyzed using Pearson Correlation procedures. Results indicated that there was a positive correlation between metacognition and critical thinking. In other words, the more metacognitive strategies increase in students, the more critical thinking enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
2
10
1
2
Order By: Relevance
“…In the case of gender differences, a considerable amount of research has observed that MA and gender are significantly correlated. Namely, the finding of this research related gender effect is in contrast with the results of the research conducted by Arrastia, Zayed and Elnagar, 2016;Byrne, 1993;Ogus and Ataseven, 2016;Liliana and Lavinia, 2011;Sadeghi, Hassani and Rahmatkhah, 2014;Sheorey and Monktari, 2001;Miller, 2000;Rozendal, Minnaert and Boekaert, 2001;Misu and Masi, 2017;Renninger, Hidi and Krapp, 1992;Sabna and Hameed, 2016;Eccles, Wigfield, Harold and Blumenfeld, 1993. As for the relation between MA and the years of prospectice teachers, the results implied that MA differs according to the years of pre-service EFL teachers. MA scores of seniors were higher than those of freshmen, sophomores, and juniors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the case of gender differences, a considerable amount of research has observed that MA and gender are significantly correlated. Namely, the finding of this research related gender effect is in contrast with the results of the research conducted by Arrastia, Zayed and Elnagar, 2016;Byrne, 1993;Ogus and Ataseven, 2016;Liliana and Lavinia, 2011;Sadeghi, Hassani and Rahmatkhah, 2014;Sheorey and Monktari, 2001;Miller, 2000;Rozendal, Minnaert and Boekaert, 2001;Misu and Masi, 2017;Renninger, Hidi and Krapp, 1992;Sabna and Hameed, 2016;Eccles, Wigfield, Harold and Blumenfeld, 1993. As for the relation between MA and the years of prospectice teachers, the results implied that MA differs according to the years of pre-service EFL teachers. MA scores of seniors were higher than those of freshmen, sophomores, and juniors.…”
Section: Discussioncontrasting
confidence: 99%
“…Further to this, MA and CTS are closely related constructs and they are not independent of each other. This finding of current research is consistent with previous studies (Magno, 2009;Magno, 2010;Semerci & Elaldı, 2014;Halpern, 1993;Choy & Cheah, 2009;Sadeghi, Hassani, & Rahmatkhah, 2014;Pithers & Soden, 2000;Kuhn & Dean, 2004;Lee, 2009;Ku & Ho, 2010;Daud & Hafsari, 2015;Mall-Amiri & Ahmadi, 2014;Halpern 1998;Nickerson 1994;Anderson, 2002;Flavel, 1976;Pintrich, Smith, Garcia, & Mc Keachie, 1993;Schoen, 1983;Kaur, 2017;Nemat & Erfani, 2014). This finding represented that metacognitive skills governs and directs critical thinking abilities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Esto será clave en el análisis crítico. Estrategias de pensamiento crítico (Sadeghi, Taghi y Rahmatkhah, 2014) 1. Cotejo de informaciones acerca de personajes y eventos.…”
Section: La Lecturaunclassified
“…Consequently, being intentional about promoting CT skills through a variety of pathways in and out of the classroom is essential (Sadeghi, Hassani, & Rahmatkhah, 2014;Larmar & Lodge, 2014). Doing so in conjunction with promoting LLL can make a meaningful difference in the development of CT and LLL skills.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%